Ordered clustering of single atomic Te vacancies in atomically thin PtTe₂ promotes hydrogen evolution catalysis - Li, Xinzhe (2023)
Exposing and stabilizing undercoordinated platinum (Pt) sites and therefore optimizing their adsorption to reactive intermediates offers a desirable strategy to develop highly efficient Pt-based electrocatalysts. However, preparation of atomically controllable Pt-based model catalysts to understand the correlation between electronic structure, adsorption energy, and catalytic properties of atomic Pt sites is still challenging. Herein we report the atomically thin two-dimensional PtTe2 nanosheets with well-dispersed single atomic Te vacancies (Te-SAVs) and atomically well-defined undercoordinated Pt sites as a model electrocatalyst. A controlled thermal treatment drives the migration of the Te-SAVs to form thermodynamically stabilized, ordered Te-SAV clusters, which decreases both the density of states of undercoordinated Pt sites around the Fermi level and the interacting orbital volume of Pt sites. As a result, the binding strength of atomically defined Pt active sites to H intermediates is effectively reduced, which renders PtTe2 nanosheets highly active and stable in hydrogen evolution reaction.